Neural interfaces at the nanoscale. (December 2008) - Pancrazio, Joseph J
Bioelectrical neural interfaces provide a means of recording the activity from the nervous system and delivering therapeutic stimulation to restore neurological function lost during disease or injury. Although neural interfaces have reached clinical utility, reducing the size of the bioelectrical interface to minimize damage to neural tissue and maximize selectivity has proven problematic. Nanotechnology may offer a means of interfacing with the nervous system with unprecedented specificity. Emergent applications of nanotechnology to neuroscience include molecular imaging, drug delivery across the BBB, scaffolds for neural regeneration and bioelectrical interfaces. In particular, carbon nanotubes offer the promises of material stability and low electrical impedance at physical dimensions that could have a significant impact on the future on neural interfaces. The purpose of this review is to present recent advances in carbon nanotube-based bioelectrical interfaces for the nervous system and discuss research challenges and opportunities.